Le projet de loi n° 106 et les droits de la personnalité : perspective et analyse prospective - Deleury, Édith (Les Cahiers de droit, 1984)
Bill 106 the purpose of which was to add the reformed Law of Persons to the Civil Code of Québec has been strongly criticized. Originally tabled in Parliament on November 17, 1982, a new draft has been prepared. The author thinks it fitting to give an overview of the main amendments proposed in this first draft and emphasizes the first title : « Les droits de la personnalité ».